2015
DOI: 10.7314/apjcp.2015.16.8.3463
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening Barriers from the Womans Perspective: a Meta-synthesis

Abstract: Background: The principal aim of health service providers in the field of breast cancer is to detect and treat lesions at an appropriate time. Therefore, identification of barriers to screening can be very helpful. The present study aimed to systematically review the qualitative studies for extracting and reporting the barriers of screening for breast cancer from the womans perspective. Materials and Methods: In this systematic review; Pubmed, Google Scholar, Ovid Scopus, Cochrane Library, Iranmedex, and SID w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 29 publications
5
48
0
3
Order By: Relevance
“…Lastly, our study examined organizational efforts to enhance rural outreach to underserved women. Our analysis did not examine the effects of well-documented patient-level barriers (cultural, psychosocial, structural) that may have hindered rural women's ability to engage the BSPAN network [34][35][36][37][38].…”
Section: Limitationsmentioning
confidence: 99%
“…Lastly, our study examined organizational efforts to enhance rural outreach to underserved women. Our analysis did not examine the effects of well-documented patient-level barriers (cultural, psychosocial, structural) that may have hindered rural women's ability to engage the BSPAN network [34][35][36][37][38].…”
Section: Limitationsmentioning
confidence: 99%
“…In the procrastination health model, procrastination is suggested to result in less frequent practice of health-promoting behaviors [30, 31]. Azami-Aghdash et al (2015) reported that procrastination was as a key obstacle to screening of breast cancer [32]. In a follow-up survey, Keely et al (2010) demonstrated that there is a neglected obstacle that affect postpartum diabetes screening rates, despite the perceived importance of screening by the patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, procrastination was the main barrier in Keely's study as well. Also, in a few studies, procrastination was reported as a key barrier to breast cancer screening (28,29).…”
Section: Discussionmentioning
confidence: 99%